2021
DOI: 10.1088/1757-899x/1062/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Parcel Tracking System Using Barcode Scanner with Verified Notification

Abstract: The emergence of electronic commerce online shopping has significantly increased the use of mail-order within Kolej University Poly-Tech Mara (KUPTM) communities. The tracking system provided by the courier services offers the status of delivery for each parcel until it reaches the designated destination. However, inefficiencies of managing the parcels at KUTPM may causing lost or misplaced. Therefore, the study offers an innovative approach where the study intended to invent a parcel tracking delivery and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…A tracking system for packages is usually accompanied by a unique parcel identity that can be the only primary hub that has been detected until the item is delivered to the specified address [4]. Due to the development of online purchasing and the requirement for the runner to post the parcel, a product's tracking system is becoming increasingly important.…”
Section: Background Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A tracking system for packages is usually accompanied by a unique parcel identity that can be the only primary hub that has been detected until the item is delivered to the specified address [4]. Due to the development of online purchasing and the requirement for the runner to post the parcel, a product's tracking system is becoming increasingly important.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Ref. [4]. discusses the development of the parcel tracking system, which is the subject of this study.…”
Section: Review Of Prior Literaturementioning
confidence: 99%
“…The results from the survey conducted showed that the majority of people still use manual methods, such as calling the conductor to check the status of their packages and other deliveries. It is due to these manual methods of operation that has led to several packages and parcels to be either misplaced or lost (Zainudin et al, 2021). The present technological era has made tracking and monitoring convenient and easy to manage in real time (Kaley et al, 2017) According to a survey conducted with regards to the willingness to deploy technology to track items such as packages and parcels; 77.5% strongly agree to the deployment of technology, 18.6% agree, 2.9% were neutral and 1% disagreed.…”
Section: Statement Of the Problemmentioning
confidence: 99%